2012
DOI: 10.1182/blood-2012-01-402370
|View full text |Cite
|
Sign up to set email alerts
|

Internalization and endosomal degradation of receptor-bound antigens regulate the efficiency of cross presentation by human dendritic cells

Abstract: Dendritic cells (DCs) can capture extracellular antigens and load resultant peptides on to MHC class I molecules, a process termed cross presentation. The mechanisms of cross presentation remain incompletely understood, particularly in primary human DCs. One unknown is the extent to which antigen delivery to distinct endocytic compartments determines cross presentation efficiency, possibly by influencing antigen egress to the cytosol. We addressed the problem directly and quantitatively by comparing the cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

22
204
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(231 citation statements)
references
References 49 publications
22
204
3
Order By: Relevance
“…Specific trafficking routes that initiate more efficient MHC I or MHC II Ag presentation have not been strictly defined. For example, DEC205 (CD205), a molecule that traffics to late endosomes (4)(5)(6), is considered a superior receptor for MHC I cross-presentation (7)(8)(9)(10). Alternatively, MHC I cross-presentation is efficiently enhanced by receptors that traffic to early, but not late, endosomes (5,6,11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specific trafficking routes that initiate more efficient MHC I or MHC II Ag presentation have not been strictly defined. For example, DEC205 (CD205), a molecule that traffics to late endosomes (4)(5)(6), is considered a superior receptor for MHC I cross-presentation (7)(8)(9)(10). Alternatively, MHC I cross-presentation is efficiently enhanced by receptors that traffic to early, but not late, endosomes (5,6,11,12).…”
mentioning
confidence: 99%
“…Furthermore, receptors that traffic to the same intracellular destination can differ in their Ag presentation efficiencies. This is the case for CD40 and mannose receptor that both traffic to early endosomes, yet for unknown reasons CD40 is more efficient at eliciting MHC I cross-presentation (5). Therefore, the emerging view is that receptor trafficking alone is not the sole determinant of the effectiveness of Ag presentation outcomes.…”
mentioning
confidence: 99%
“…Other studies have shown that soluble Ags are cross-presented through the TAP-dependent cytosolic pathway (9,10) or the TAPindependent vacuolar pathway (4,10). In particular, Ags conjugated to Abs are targeted to either the early or the late endosome through CD40, the mannose receptor, or DEC205 (11). Efficient cross-presentation is mediated by either prolonged residence of the Ag in the early endosome or decreased degradation in the late endosome (11)(12)(13).…”
mentioning
confidence: 99%
“…In particular, Ags conjugated to Abs are targeted to either the early or the late endosome through CD40, the mannose receptor, or DEC205 (11). Efficient cross-presentation is mediated by either prolonged residence of the Ag in the early endosome or decreased degradation in the late endosome (11)(12)(13). Dendritic cell (DC) cross-priming of the TLRmediated CTL response during microbial infection may not only upregulate costimulatory molecules but also regulate this process of cross-presentation (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…In humans, MoDCs express high levels of MR whereas CD1c + DCs and CD141 + DCs express little if any MR [21,22], which may account for the lower uptake of soluble protein by CD1c + DCs and CD141 + DCs and suggests that similar uptake mechanisms occur between species. Consistent with their known higher levels of lysosomal proteases [22,23] the proteasome for processing of the pp65 NLV epitope, suggesting preferential use of the vacuolar pathway by MoDCs. This is further corroborated by studies demonstrating preferential use of the vacuolar pathway by mouse MoDCs and their in vitro BM-derived equivalent for cross-presentation of soluble protein [20,24], suggesting conservation of these pathways between species.…”
mentioning
confidence: 99%